GIARDIA LAMBLIA INFECTION: REVIEW OF CURRENT DIAGNOSTIC STRATEGIES FOR CHILDREN (Academia Science Repository, 2023)
Giardiasis has a global distribution and it is a common cause of diarrhea in both children and adults and is transmitted via the fecal-oral route through direct or indirect ingestion of cysts. The laboratory diagnosis of Giardia spp. is mainly based on demonstration of microscopic cyst or trophozoite in stool samples but several immunological-based assays and molecular methods are also available for giardiasis diagnosis. The aim of this study was to conduct a review of the applied methods in medical laboratory and to highlight pitfalls and challenges of them for diagnosis of giardiasis. In this article we have evaluated the Giardia diagnostic methods with a broad review of literature, electronic databases and books. The search has covered the articles and some textbooks that have published up to 2018.It has been concluded that traditional microscopy combination with stool concentration method should still be held in the routine medical laboratory due to economical and high sensitivity and immunological-based assay and molecular methods which are recommended to use as a complementary test to the traditional technique.